2020
DOI: 10.1073/pnas.2008741117
|View full text |Cite
|
Sign up to set email alerts
|

The porphyrin ring rather than the metal ion dictates long-range electron transport across proteins suggesting coherence-assisted mechanism

Abstract: The fundamental biological process of electron transfer (ET) takes place across proteins with common ET pathways of several nanometers. Recent discoveries push this limit and show long-range extracellular ET over several micrometers. Here, we aim in deciphering how protein-bound intramolecular cofactors can facilitate such long-range ET. In contrast to natural systems, our protein-based platform enables us to modulate important factors associated with ET in a facile manner, such as the type of the cofactor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 51 publications
5
40
0
Order By: Relevance
“…In the case of the Zn-azurin and for the Apo, part of the contribution to the transmission at the Fermi level seems indeed to be provided by these residues as well. As an aside, it is worth mentioning that recent experiments on protoporphyrins have revealed that the metal redox center has no role in the electron transfer, which was instead found to be mediated solely by the conjugated backbone of the molecule [68]. Our results are based on DFT, which is known to be affected by uncertainties concerning the size of the HOMO-LUMO gap because of self-interaction errors in the standard exchange-correlation functionals and image charge effects [69][70][71][72][73][74].…”
Section: X=nimentioning
confidence: 84%
“…In the case of the Zn-azurin and for the Apo, part of the contribution to the transmission at the Fermi level seems indeed to be provided by these residues as well. As an aside, it is worth mentioning that recent experiments on protoporphyrins have revealed that the metal redox center has no role in the electron transfer, which was instead found to be mediated solely by the conjugated backbone of the molecule [68]. Our results are based on DFT, which is known to be affected by uncertainties concerning the size of the HOMO-LUMO gap because of self-interaction errors in the standard exchange-correlation functionals and image charge effects [69][70][71][72][73][74].…”
Section: X=nimentioning
confidence: 84%
“…Long-range charge transport has been reported in the G. Sulfurreducens bacteria up to a micrometer scale 54 . Studies have shown that the geobacteria's long-range transport cannot be replicated by solely using hopping or coherent transport mechanisms 55 .…”
Section: Modular Chainsmentioning
confidence: 99%
“…Studies have shown that the geobacteria's long-range transport cannot be replicated by solely using hopping or coherent transport mechanisms 55 . Newly-proposed mechanisms have been suggested based on the alternating rigidity of the protein conducting the charge in biological nanowires 54,56 . Inspired by biological nanowires, in this section, we explore the use of probe "blocks" to mimic modular nanowires of alternating rigidity and study the resulting effect on the resistance of the system.…”
Section: Modular Chainsmentioning
confidence: 99%
See 2 more Smart Citations